A defective g-C3N4/RGO/TiO2 composite from hydrogen treatment for enhanced visible-light photocatalytic H2 production. Issue 43 (4th November 2020) - Wang, Jing; Sun, Youcai; Fu, Lijun; Sun, Zhuang; Ou, Man; Zhao, Shulin; Chen, Yuhui; Yu, Fengjiao; Wu, Yuping
Abstract : g-C3 N4 /RGO/TiO2 with nitrogen and oxygen vacancies possesses an efficient H2 evolution rate, which exceeds that of g-C3 N4 /RGO/TiO2 without vacancy defects. Abstract : Photocatalytic H2 evolution is a clean technology to alleviate energy and environmental issues. The limited light absorption and the separation efficiency of photogenerated charge carriers are the major hurdles constraining the application of numerous photocatalysts. Herein, we report a simple and effective strategy, a multistep heat-treatment method, to synthesise a defective g-C3 N4 /RGO/TiO2 composite to increase its rate of activity for H2 production. The defects, nitrogen and oxygen vacancies, are simultaneously introduced on the surface of the g-C3 N4 /RGO/TiO2 composite. The vacancy defects essentially endow g-C3 N4 /RGO/TiO2 with a boosted photocatalytic H2 evolution rate (4760 μmol h −1 g −1 ) under visible-light irradiation, which is higher than that of the most of g-C3 N4 /TiO2 composites. This is attributed to the improved visible-light absorption as well as the separation and transfer rate of photogenerated charge carriers arising from vacancy defects. This study may provide an avenue for preparing defective photocatalysts for efficient H2 evolution.